Reproductive strategies of a population of a freshwater amphipod (Crustacea, Amhipoda, Hyalellidae) from southern Brazil - Castiglioni, Daniela da Silva; Streck, Morgana Taís; Rodrigues, Stella Gomes; Bueno, Alessandra Angélica de Padua (Biota Neotropica, 2018)
Abstract: The aim of this study was to characterize the reproductive strategies of a population of Hyalella bonariensis from southern Brazil. Pairing success, reproductive period of males and females, fecundity, and body size at the onset of reproduction were evaluated. Animals were sampled four times (August 2012, October 2012, January 2013, and April 2013) with the 250 µm-mesh dip net during 20 minutes by only one person. In the field, precopulatory pairs and ovigerous females were individualized. In the laboratory, cephalothorax length (CL) were measured and eggs and juveniles were removed from the females' marsupium and counted. The mean CL of paired males and females was significantly higher than that of non-paired males and females. A sexual dimorphism in body size was observed in the population - both paired and non-paired males were larger than females. Probably larger males have a higher probability of losing females during precopulatory behavior. A significant correlation was observed between the size of paired males and females - larger males often paired with larger females and smaller males paired with smaller females (r = 0.81). The pairing success of males increased with body size and we can assume that males from all size classes are able to find mates. The pairing success of females was independent of body size - paired and non-paired females had similar mean CL. The reproductive success increased with body size in males and females, and was more evident in males. Females from the largest size classes had null reproductive success. The idea that larger females can produce more eggs but might have a lower probability of finding a mate than smaller females was corroborated by our results. Therefore, smaller females have higher pairing success because they are capable of mating with a higher percentage of males. The estimated mean fecundity of H. bonariensis was 17.4 (± 3.89) eggs/juveniles. Our results are similar to those of other species of Hyalella from Brazil.